COMPARATIVE CHARACTERISTIC OF STRUCTURAL FEATURES OF FLY OF NIGHT INSECTS OF TYULENIY AND NORDOVIY ISLANDS IN THE NORTH CASPIAN OF DAGHESTAN REPUBLIC - G. M. ABDURAKHMANOV; G. M. NAKHIBASHEVA; S. M. KLYCHEVA; S. T. MAGOMEDOVA; S. M. ELDERKHANOVA; S. N. ESKENDAROVA (Юг России: экология, развитие, 2015)
Comparative characteristic of structural features of fly of night insects of Tyuleniy and Nordoviy islands in the North of Caspian Sea is made in the work